The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7448/ias.19.1.20875
|View full text |Cite
|
Sign up to set email alerts
|

Stated product formulation preferences for HIV pre‐exposure prophylaxis among women in the VOICE‐D (MTN‐003D) study

Abstract: IntroductionThe effectiveness of HIV pre-exposure prophylaxis (PrEP) requires consistent and correct product use, thus a deeper understanding of women's stated product formulation preferences, and the correlates of those preferences, can help guide future research. VOICE-D (MTN-003D), a qualitative ancillary study conducted after the VOICE trial, retrospectively explored participants’ tablet and gel use, as well as their preferences for other potential PrEP product formulations.MethodsWe conducted an analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 30 publications
(53 reference statements)
3
57
1
Order By: Relevance
“…Similar results were reported among adolescent users of the contraceptive NuvaRing in the United States . Other studies in Africa have likewise identified that familiarity with a delivery method is correlated to preference . Product developers and researchers should therefore be mindful that introduction of a novel method may face initial resistance, but these opinions may be amenable to change through provision of information, support and practice in use of the method through introductory use periods.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results were reported among adolescent users of the contraceptive NuvaRing in the United States . Other studies in Africa have likewise identified that familiarity with a delivery method is correlated to preference . Product developers and researchers should therefore be mindful that introduction of a novel method may face initial resistance, but these opinions may be amenable to change through provision of information, support and practice in use of the method through introductory use periods.…”
Section: Discussionsupporting
confidence: 68%
“…The findings of both studies highlight the importance of conducting multisite research to assess the generalizability of findings across settings. Furthermore, the fact that there were country differences, and that the distribution of products chosen and ranked number one was fairly evenly distributed support the findings of other research studies and the call for continued research and development of a range of options for women, a priority that has been threatened by funding cuts, fears of expensive registration trials, and false assumptions about what methods women will use . The contraceptive field can offer important parallels: as the method mix for modern contraception has increased in Sub‐Saharan Africa, so has the overall proportion of users .…”
Section: Discussionsupporting
confidence: 57%
“…Acceptability research conducted since VOICE and FEM‐PrEP indicate that women desire low burden prevention strategies that are compatible with their lifestyles and provide peace of mind . Indeed, a daily pill regimen can be both logistically and emotionally burdensome (as it may remind women about HIV or IPV) .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a daily pill regimen can be both logistically and emotionally burdensome (as it may remind women about HIV or IPV) . When offered HIV prevention alternatives through discrete choice experiments which assess hypothetical preferences and trade‐offs between them, women prefer longer‐acting and more adherence “forgiving” products, supporting the development of a range of PrEP delivery modalities – ring, injectable, implantable – from which young women can choose . In parallel with development of formulations with less frequent dosing, it is important to learn about delivery and use of oral PrEP, a vanguard product.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, findings from our research published in an earlier paper showed that amongst a range of eight modes of delivery for biomedical HIV prevention products (cervical barrier, implants, injectables, oral tablets, vaginal gel, vaginal film, vaginal ring, and vaginal suppository), gels did not rank highly in product preference ratings (Luecke et al, 2016). Women perceived gels to create uncomfortable sensations of being wet and leaky.…”
Section: Introductionmentioning
confidence: 85%